Conceptualization and development of a scale for brand experience in extended reality - Joo-Eon Jeon (Global Business & Finance Review (GBFR), 2023)
Purpose: This study aims to conceptualize the brand experience that users' avatars can experience on an XR platform and develop items to measure it. Design/methodology/approach: The author presents both a conceptual analysis of brand experience in XR (BXIXR) and a BXIXR scale by conducting a review of marketing research and immersive technology. Adhering to the relevant theory and psychometric principles, the BXIXR scale was developed and validated through a literature review and item generation process, followed by confirmatory factor analysis, reliability analysis, and predictive validity testing. Findings: This research demonstrates that BXIXR can be broken down into four dimensions that are differentially evoked by various brand spaces in XR: search, entertainment, relations, and assembly. Research limitations/implications: This research suggested that the brand experience that users have at the boundary between the physical and virtual worlds may differ from brand experience in the physical world. In this study, it is expected that meaningful implications can be proposed in that it attempts to derive a brand experience based on an immersive economy. Originality/value: The results of this study suggest that the BXIXR scale is a reliable and valid measure of BXIXR. The four-factor structure of the scale is consistent with the theoretical framework, and the results of the reliability and validity testing provide evidence for its robustnes.
Keywords: 650; Extended reality; Brand experience; Virtual store; Immersive technology; Engagement